MRI pattern characterization of cerebral cardioembolic lesions following atrial fibrillation ablation - Saglietto, Andrea; Bertello, Eleonora; Barra, Marina; Ferraro, Ilenia; Rovera, Chiara; Orzan, Fulvio; De Ferrari, Gaetano Maria; Anselmino, Matteo (Frontiers in Cardiovascular Medicine, 2024)
Background: Recognizing etiology is essential for treatment and secondary prevention of cerebral ischemic events. A magnetic resonance imaging pattern suggestive for an embolic etiology has been described but, to date, there are no uniformly accepted criteria. Aim. The purpose of the study is to describe MRI features of ischemic cerebral lesions occurring after transcatheter ablation of atrial fibrillation (AF). Methods. A systematic review and meta-analysis of studies performing brain imaging investigations before and after AF transcatheter ablation was performed. Incidence of cerebral ischemic lesions after AF transcatheter ablation was the primary endpoint. The co-primary endpoints were the prevalence of the different neuroimaging features regarding the embolic cerebral ischemic lesions. Results. 25 studies, encompassing 3304 patients, were included in the final analysis. The incidence of ischemic cerebral lesions following AF transcatheter ablation was 17.2% (95% CI 12.2-23.8%), of which a minimal fraction was symptomatic (0.60% [95% CI 0.09-3.9%]). Only 1.6% of the lesions (95% CI 0.9-3.0%) had a diameter > 10 mm and in 20.5% of the cases the lesions were multiple (95% CI 17.1-24.4%). Brain lesions were equally distributed across the two hemispheres and the different lobes; cortical location was more frequent (64.0% [95% CI 42.9-80.8%]) while middle cerebral artery territory was the most involved 37.0% (95% CI 27.3-48.0). Conclusions. The prevailing MRI pattern comprises a predominance of small (< 10 mm) cortical lesions, more prevalent in the territory of the middle cerebral artery.